Perbandingan Pengaruh Antara Massage Dengan Ice Massage Untuk Mencegah Terjadinya Nyeri Akibat Delayed Onset Muscle Soreness Pada Otot Hamstring Sesudah Latihan Lying Leg Curl - Atmaja, Amirudin Dwi, Maskun Pudjianto, SMPh, M.Kes (2016)
Background: Exercise is an activity that can support physical development ,exercise with weights is often used for muscle strenthening one of them is lying leg curl exercise. The problematic after Lying leg curl exercise is Delayed onset muscle soreness (DOMS), DOMS is pain in the muscles that appear 24-48 hours after exercise. DOMS symptoms often occur in people who are not accustomed to the sport, especially sports that require extra muscle contraction. Objective: To determine the effect of ice massage and massage to prevent pain caused by DOMS after exercise and to determine the difference between the effect of ice massage and massage to prevent pain caused by DOMS. Benefits Research: To determine the effect of ice massage and massage to prevented pain after exercise caused by DOMS and knowing the difference between the provision of ice massage and massage to prevented pain after exercise caused by DOMS. Methods: The study is a quasi experimental approach experimental and research design pre and post test two group design. Sampling technique is purposive sampling. Number of samples 20 Students. RESULTS: This study uses a measuring instrument in the form of pain Visual Analoge Scale (VAS). Based on statistical test paired sample t-test showed the effect of ice massage with significant value 0.000 <0.005 (p) and the effect of massage with sigifikasi value 0.000 <0.005 (p) .In statistical test Independent sample t-test on the get the result of differences between ice massage and massage where sigifikasi 0.008> 0.05 (p). Conclusion: The existence of the effect of ice massage and massage to reduce pain caused by DOMS after exercise and the difference between the effect of ice massage and massage to relieve pain after exercise due DOMS keywords: Ice massage, Massage, Delayed Onset Muscle Soreness